Reviving a national strategy roadmap for organ and tissue donation in South Africa - Thomson, David; Muranda, Albert Z (African Journal of Nephrology, 2023)
In September 2019, a two-day workshop ahead of the Southern African Transplantation Society congress brought together South African champions for organ donation and leaders from the International Society of Organ Donation and Procurement (ISODP) at a high-level workshop focused on creating a national strategy roadmap to improve organ donation in South Africa. The full report is available via the supplementary materials on the African Journal of Nephrology website.